Human resource management : a contemporary approach - Beardwell, Ian (Prentice Hall Financial Times, 2004)
Human Resource Management is in line with CIPD standards and the critical approach and writing style is suitable for undergraduates, HRM Masters students and specialist MBAs."--BOOK JACKET Print Book, English, 2004.